Broadcasting the Past: The Monash Thai Music Collection. Issue 2 (2nd July 2016) - Mitchell, James Leonard
Abstract : Monash University possesses a unique collection of Thai music sound recordings, the majority of which originally belonged to the Thai broadcasting service of Radio Australia. The 932 gramophone records are in 78 rpm, 45 rpm and 33 rpm formats dating from 1950 to 1985, covering almost every Thai music genre from that period. This description and analysis considers whether the collection is historically and culturally representative, and what its scope might reveal about Thai/Australian relations and Radio Australia during the period in which it was assembled. The collection's monetary, cultural and scholarly value is assessed along with recommendations on how it could be expanded and managed into the future.